2015
DOI: 10.3892/ol.2015.3084
|View full text |Cite
|
Sign up to set email alerts
|

Nipple-sparing mastectomy in breast cancer patients: The role of adjuvant radiotherapy (Review)

Abstract: Abstract. The present study aimed to evaluate the role of adjuvant radiotherapy (RT) following nipple-sparing mastectomy (NSM) for patients with ductal carcinoma in situ and invasive breast cancer, based on the published literature. Currently, there is no standard for RT following NSM. NSM aims to spare the nipple areola complex (NAC) without compromising locoregional control. Long-term follow-up studies have begun to show promising results. A search of the English literature was performed using the Medline da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…However, NAC and skin flap ischemia and necrosis can occur and result in morbidity to the patient. Previous studies have reported various patient, clinical, and surgical factors, such as age, smoking history, and type of surgical incision, that are associated with ischemic and necrotic complications after NSM (2,9,14,15,19,21,22). Our study is unique in that it addresses vascular features on pre-operative MRI that are predictive of ischemic and necrotic complications.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…However, NAC and skin flap ischemia and necrosis can occur and result in morbidity to the patient. Previous studies have reported various patient, clinical, and surgical factors, such as age, smoking history, and type of surgical incision, that are associated with ischemic and necrotic complications after NSM (2,9,14,15,19,21,22). Our study is unique in that it addresses vascular features on pre-operative MRI that are predictive of ischemic and necrotic complications.…”
Section: Discussionmentioning
confidence: 67%
“…Several factors associated with NAC and skin flap ischemia and necrosis have been reported, including age, body mass index (BMI), smoking history, hypertension/diabetes mellitus, pre-operative radiation therapy, oncologic indication for NSM, breast volume, type of incision, reconstruction approach, and NAC involvement with areola flap thickness less than 5 mm (2,9,14,15,19,21,22,25). To our knowledge, however, there are no published studies on the vascular supply to the breast, as characterized by pre-operative MRI, and its association with NAC and skin flap ischemia and necrosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 17 studies analysed by Janssen et al [ 29 ] in 2015, only seven provided a detailed description of the radiotherapy modalities. In most studies, the delivered dose was 50 Gy.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, rates of CPM are also on the rise for both invasive and in situ cancer (1,6,7). There are several reasons for these phenomena, including the increasing use of preoperative MRI, the growing employment of immediate post-mastectomy reconstruction, improvements in cosmetic results with the relatively new techniques of skin-and nipple-sparing mastectomy, the increasing use of genetic testing, and last but not least, the patients' entitlement to choose their preferred surgery option (6)(7)(8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%